The Italian Society for Digestive Endoscopy (SIED) accreditation and quality improving project based on international standards - Giancarlo Spinzi; Angelo Milano; Piero Brosolo; Paola Da Massa Carrara; Maurizio Labardi; Alberto Merighi; Luisa Riccardi; Francesco Torresan (Endoscopy International Open, 2020)
Background and study aims Accreditation of endoscopy services, using valid quality indicators, may address failures to comply with quality standards between endoscopy services. The aim of this work was to present the Italian Society for Digestive Endoscopy (SIED) accreditation model and its effectiveness. Methods A team of eight endoscopists identified quality indicators derived from international guidelines and assessed them in each center voluntarily requesting accreditation. During a 1-day site visit, two expert endoscopists, the representative of the independent and international administrative certification body and a professional nurse evaluated the endoscopy center, by direct observation of the endoscopy team and examination of the medical records Results In all centers we noted shortcomings in instrument reprocessing. In 30 of 40 centers (75 %) the information in the nursing charts was incomplete. Sampling for Helicobacter pylori had not been done in 12 of 40 centers (30 %). In six of 40 centers (15 %) the adenoma detection rate for each endoscopist had not been evaluated. Post-polypectomy intervals were inappropriate in 12 of 40 centers (30 %). We noted a statistically significant difference (P < 0.001) between the answers to the SIED checklist of indicators submitted to the inspection team for accreditation before the site visit and the situation found for colonoscopy on site. As of June 30, 2018, 18 endoscopy centers had been accredited and 10 centers had not yet being accredited because they had not completed the measures to correct points raised at the visits. Conclusions Numerous Italian endoscopy centers fail to meet important quality indicators. Our accreditation program can provide means for detecting these problems and correcting them by implementing SIED standards.